An exploratory study of the experiences of refugees receiving assistance from Non-Profit Organisations (NPOs) in the City of Cape Town Metropolitean Area - Ngwara, Kudzai (Department of Social Development, 2021)
The plight of refugees has become a global social problem due to continuous political unrest, war and natural disasters worldwide. People are forced to migrate to other countries for safety and better living conditions in the hope that their basic human rights will be upheld. However, many destinations chosen by refugees face social problems of their own and are failing to provide basic services to citizens leaving the onus of service provision on charitable or Non-Profit Organisations (NPOs). South Africa is no exception as it has become a popular destination for refugees from other African countries and Asia but is not able to adequately provide for their needs. In this situation, NPOs have taken a central role in ensuring refugees are integrated into the South Africa society. This exploratory research examined the experiences of refugees accessing services from NPOs in Cape Town. A qualitative design and purposeful sampling are used to delve deeper into the experiences of refugees to amplify their voices about service provision. Refugees from six different NPOs in Cape Town namely: Adonis Musati Project, Triangle Project, PASSOP, MRASA, VIDEFI and Kwesu Women's organisation were interviewed about their experiences of accessing services. Participants had to be recipients of one or more of the services from any of the NPOs chosen for the research study. Their experiences related to the benefits and challenges faced when accessing services from NPOs and negotiating and navigating the challenges faced in accessing services from NPOs. The study revealed that refugees benefit from services offered to them although the challenges outweigh the benefits due to lack of funding and failure to provide adequate resources. The refugees mainly needed services to help them secure employment, documentation, and access to healthcare and basic education. They needed referrals to access these services from other NPOs or government institutions otherwise it was difficult to obtain. The refugees shared their experiences and on this basis recommendations on improving the services needed to ensure basic human rights are included in this study.